Waiting for morning - Kingsbury, Karen (Kingsbury, Karen. Forever faithful series., 1999)
As Hannah Ryan waits for her family to return home form a camping trip, she realizes she has everything going for her - a husband other women admire, two charming teenage daughters, and a loving Christian home. As the sunny afternoon turns into twilight, her uneasiness grows along with the shadows. Then a car pulls into Hannah's driveway, bring two police officers ... and devastating news that shatters her life forever.